FREQUENCY OF UROLOGICAL CARCINOMA IN PATIENTS PRESENTING WITH GROSS HAEMATURIA - HAMID, H; GHANI, A; FAROOQ, K; ULLAH, R; BEGUM, F; KHAN, IA (Biological and Clinical Sciences Research Journal, 2023)
Gross haematuria is one of the most prevalent urological conditions with a high risk of morbidity and death. Numerous studies showed that people with gross haematuria had a greater chance of acquiring urological carcinomas and those with gross haematuria had a high incidence of malignant cells. The current study was carried out to determine the frequency of urological carcinoma amongst patients presenting with gross haematuria. The current study was cross-sectional, done at the Urology Department Khalifa Gul Nawaz Teaching Hospital for six months from January 2023 to June 2023. In the current study, 170 patients were enrolled. Age, gender, place of residence, and socioeconomic level were all noted for patients. All the collected data was analyzed by using 23 version of SPSS. A total of 170 patients were enrolled in the current study. The male participants were 128 (75.29%) and female patients were 42 (24.71%. Most of the patients 82 (48.23%), were 40-50 years old. The frequency of urological carcinomas was observed in 29 (17.06%). According to the findings of our investigation, urological carcinoma is a common problem. The most prevalent causes of gross haematuria were urinary tract infections and trauma. Since urothelial tumors may be efficiently handled with a better long-term result if found early, general practitioners should order an ultrasound scan for individuals presenting with gross haematuria.